PENGARUH CURRENT RATIO (CR) DAN RETURN ON EQUITY (ROE) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PT XYZ PERIODE 2012-2021 - Sulaeman, Dede (JUBISMA, 2024)
This study aims to determine whether there is an influence of the Current Ratio (X1) on the Price to Book Value (Y). The research design used in this research is the associative research design. Source data obtained through website www.idx.co.id period 2012-2021. Data analysis used is ratio analysis, double linear regression analysis assisted by SPSS version 18. The results show that the Current Ratio (X1) shows a positive and significant influence on the Price to Book Value (Y) can be seen from the thitung results > ttable (6,207 > 2,024). The Return on Equity (X2) shows a significant and positive effect on the price to book value (Y), as seen in the thinning results > tables (2,964 > 2,024. Simultaneously, the variables Current ratio and Return of Equity influenced the Price-to-Book Value(Y) from the calculations > Ftable (20,352 > 3,25). Based on the results of the study, it can be concluded that the variable Current Relation(X1) and the return on equity (X2) have an influence over the price of book value(Y). Keywords: Current Ratio, Return on Equity, Price to Book Value